Social Responsibility in Business - Sadewa, Dahva Puja; Mulyani, Ana Susi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Dynamic environmental changes due to internal and external factors force business people not only to increase profits and employment systems, but also to overcome social problems. The greater power an entrepreneur has, the greater his influence on the quality of life of society, both individually and in society. It even impacts every life in the world. This phenomenon gave rise to statements of corporate social responsibility (CSR). CSR emphasizes that corporate responsibility does not only apply to economic activities (generating profits for the sustainability of the company), but also social responsibility, including the environment. Social responsibility in business does not only focus on social responsibility that prioritizes humanism, love, concern for religion and morality, but also on the obligations that must be fulfilled by business. To solve social problems. Many things have been done consciously in developing CSR. This means that implementing CSR means investing in the development and continuity of a company, which is seen as a benefit, not a cost. CSR is still a global trend.